ANALISIS TEMA DAN AMANAT DALAM NOVEL “MARIPOSA” KARYA LULUK HIDAYATUL FAJRIYAH - Wuni Nurfauziah; Ika Mustika; Agus Priyanto (IKIP Siliwangi, 2022)
Literary work is an essay that evokes feelings, thoughts, and experiences that are poured into writing. Novel is one of the literary works created by the author's imagination which is written in a narrative and contains stories about the problems of one's life. Every novel has intrinsic elements, such as theme and message. These elements can attract the interest of readers who come from various circles. The analysis of the novel in this study aims to describe the themes and messages contained in the novel